Biodegradation characteristics and genomic functional analysis of indole‐degrading bacterial strain Acinetobacter sp. JW. Issue 4 (26th November 2018) - Zhang, Xuwang; Jing, Jiawei; Zhang, Lizhi; Song, Zhaojian; Zhou, Hao; Wu, Minghuo; Qu, Yuanyuan; Liu, Lifen
Abstract: BACKGROUND: Indole, an important type of N ‐heterocyclic aromatic compound, is considered a toxic and odorous pollutant in coking and municipal wastewater. For efficient bioremediation of indole‐containing wastewater, an indole‐degrading bacterial strain JW was isolated from activated sludge in this study. The indole biodegradation characteristics and the whole‐genome sequence of strain JW were also determined. RESULTS: Strain JW, capable of utilizing indole as the sole carbon and nitrogen source, was identified as Acinetobacter sp. based on 16S rRNA gene sequence analysis. It was able to completely degrade 100 mg L −1 indole within 20 h, and transform organic nitrogen to ammonia (NH4 + ‐N) and nitrate (NO3 − ‐N). Meanwhile, strain JW also presented high capacity for indole degradation at a range of initial indole concentrations (25–200 mg L −1 ) and pH (6.0–8.0). The key metabolites during indole biodegradation were identified by liquid chromatography coupled to Q‐Exactive high resolution mass spectrometry, and included isatin, anthranilate, salicylate, catechol and indigo. The whole‐genome sequence of strain JW revealed the possible functional genes related to indole biodegradation, such as iif genes, ant genes and downstream metabolic genes. Thus, an indole biodegradation mechanism was proposed based on metabolites identification and genomic analysis. CONCLUSION: The results suggested that Acinetobacter sp. JW could be a promising biological candidate for bioremediation of indole, and the useful genetic information might enrich our understanding of microbial degradation of indole. © 2018 Society of Chemical Industry